Extendable piezo/ferroelectricity in nonstoichiometric 2D transition metal dichalcogenides - Hu, Yi (2024)
Engineering piezo/ferroelectricity in two-dimensional materials holds significant implications for advancing the manufacture of state-of-the-art multifunctional materials. The inborn nonstoichiometric propensity of two-dimensional transition metal dichalcogenides provides a spiffy ready-available solution for breaking inversion centrosymmetry, thereby conducing to circumvent size effect challenges in conventional perovskite oxide ferroelectrics. Here, we show the extendable and ubiquitous piezo/ferroelectricity within nonstoichiometric two-dimensional transition metal dichalcogenides that are predominantly centrosymmetric during standard stoichiometric cases. The emerged piezo/ferroelectric traits are aroused from the sliding of van der Waals layers and displacement of interlayer metal atoms triggered by the Frankel defects of heterogeneous interlayer native metal atom intercalation. We demonstrate two-dimensional chromium selenides nanogenerator and iron tellurides ferroelectric multilevel memristors as two representative applications. This innovative approach to engineering piezo/ferroelectricity in ultrathin transition metal dichalcogenides may provide a potential avenue to consolidate piezo/ferroelectricity with featured two-dimensional materials to fabricate multifunctional materials and distinguished multiferroic.